2000
DOI: 10.1007/s000140050133
|View full text |Cite
|
Sign up to set email alerts
|

Universal octonary diagonal forms over some real quadratic fields

Abstract: Abstract. In this paper, we will prove there are infinitely many integers n such that n 2 − 1 is square-free and Q( √ n 2 − 1) admits universal octonary diagonal quadratic forms. Mathematics Subject Classification (2000). Primary 11E12, Secondary 11E20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…Roughly speaking, if K = Q( √ D) has small class number, it contains many integers of small norm, and we will see that this often forces a universal form to have many variables. On the other hand, Kim [Ki2] showed that there are infinitely many real quadratic fields that admit universal quadratic forms in 8 variables; these fields are all of the form Q( √ n 2 + 1) and have in particular very large class number.…”
Section: Theorem 1 Given Any Positive Integer M There Exist Infinimentioning
confidence: 99%
“…Roughly speaking, if K = Q( √ D) has small class number, it contains many integers of small norm, and we will see that this often forces a universal form to have many variables. On the other hand, Kim [Ki2] showed that there are infinitely many real quadratic fields that admit universal quadratic forms in 8 variables; these fields are all of the form Q( √ n 2 + 1) and have in particular very large class number.…”
Section: Theorem 1 Given Any Positive Integer M There Exist Infinimentioning
confidence: 99%
“…It may seem that the number of variables required by a universal quadratic form should grow with the discriminant of the (real quadratic) number field. This is not entirely true, as Kim [7] constructed an infinite family of fields of the form Q( √ n 2 − 1) admitting positive diagonal octonary universal forms.…”
Section: Introductionmentioning
confidence: 99%
“…All positive definite ternary universal forms over real quadratic fields were determined in [3]. Further developments on universal forms over totally real number fields were established by B. M. Kim (see [12], [13] and [14]). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bhargava and Hanke enunciated that they proved the 290-conjecture which characterizes the universality of (nonclassical) quadratic forms. That is, if a (nonclassical) quadratic form represents the 29 numbers, 1, 2, 3, 5,6,7,10,13,14,15,17,19,21,22,23,26,29,30,31,34,35,37,42,58,93,110,145,203,290, then it is universal (see [9]). One can use this theorem to prove the universality of a Hermitian lattice.…”
Section: Introductionmentioning
confidence: 99%